ANALISI YURIDIS PROSES PEMISAHAN HAK PADA TANAH YANG BERSTATUS HAK GUNA USAHA MENJADI HAK GUNA BANGUNAN UNTUK AREAL INDUSTRI PABRIK PENGOLAHAN KELAPA SAWIT PADA PT.TALES INTI SAWIT ( STUDY DI PT.TALES INTI SAWIT ) - SRI WAHYUNI DAULAY (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd Yamin2. Syafruddin Kalo3. Edy Ikhsan PT. Tales Inti Sawit is a company which operates in PKS (Oil Palm Processing) Plant established with Memorandum of Association No. 28 on August 11, 2003 which has gotten the validity from the Minister of Justice and Human Rights No. C-30204 HT.01.01.TH.2003 on December 30, 2003 . The HGB was from HGU (Leasehold) owned by PT. Tamiang Sari in the area of 20 hectares of the total 494.57 hectares. The establishment of PT. Tales Inti Sawit was from the cooperation agreement between PT .Tamiang Sari and PT. Duta Marga Lestarindo. The transaction was bound in a contract under NJOP (Taxable Value of Property), followed by investing the capital. Meanwhile, according to Tax Law No. 16/2009, the basis for tax assessment is the true/appropriate transaction value which is in accordance with the value the sales object in the transaction. The research used juridical normative and descriptive method, using primary data supported by secondary and tertiary data. The data were gathered by conducting library research and interviews. The result of the analysis showed that BPN RI (National Land Agency) had implemented the process of the request for the right and title transfer of the Process of Request for Separation a part of HGU owned by PT. Tamiang Sari which had implemented even though its procedure was complicated and took a long time by the permit of releasing a part of HGU No. 14-V.B-2004 and was bound in a Sales Binding Contract with the price below NOJP. In fact, the agreement about the price was made underhandedly.Keywords: Request for the Right, Right Transfer, National Land Agency Office